Conquering Communication Barriers: The English Quarantine Al Badriyah Program to Enhance Speaking Skills - Sukmojati, Edi; Rahmat, Hery (Universitas Siliwangi, 2024)
Amidst the rapidly evolving global landscape, proficiency in English language skills has become indispensable for accessing information, facilitating effective communication, and engaging in global interactions. This necessity is particularly pronounced for students in Lombok who actively participate in diverse sectors such as agriculture, academia, and trade. Understanding the importance of English proficiency in these contexts, this study explores the communication barriers experienced by students during their learning process. It investigates the underlying factors that impede the development of their speaking skills. The qualitative study involved eighteen participants enrolled in the English Quarantine Al Badriyah (EQAB) Program, with eight selected as primary informants for detailed interviews. Data collection methods included closed-ended questions and semi-structured interviews, which were meticulously transcribed and analysed using data reduction, data display, and conclusion-drawing techniques. The research revealed several significant barriers hindering students’ English-speaking skills, including nervousness, lack of vocabulary, and shyness. Conversely, the study identified motivation factors, positive feedback and agreeable activities as pivotal elements that could effectively enhance students’ speaking proficiency. This study underscores the critical role of English language proficiency in empowering students to overcome barriers and actively participate in global discourse. By addressing these challenges and leveraging supportive factors, educators and stakeholders can better facilitate the development of robust English communication skills among students in diverse educational and professional settings.Keywords: Communication Barriers; Enhancing English; Speaking Skills.